Anti-Japanese Encephalitis virus (JEV) activity of triterpenes and flavonoids from Euphorbia hirta - Tayone, Wilanfranco C.; Morita, Eiji; Arakawa, Masashi; Tayone, Janeth C.; Goto, Simon; Ishida, Kotaro; Hashimoto, Masaru (2020)
Chemical investigation of Euphorbia hirta, a folkloric medicinal plant against dengue in the Philippines, disclosed two known flavonoids (quercetrin and myricitrin) together with seven known triterpenes (taraxerone, taraxerol, β-sitosterol, 24-hydroperoxycycloart-25-en-3β-ol, 25-hydroperoxycycloart-23-en-3β-ol, lupeol, and (23E)-cycloart-23-en-3β, 25-diol). The structures were established mainly with 1H and 13C nuclear magnetic resonance (NMR) spectroscopic analyses in comparison with the literature data. These compounds were tested against Japanese encephalitis virus (JEV). Results showed that myricitrin exhibited good inhibition on the production of the infectious viral particle at 100 μM. (Author's abstract)